2022
DOI: 10.1002/anie.202206482
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐High Temperature Molten Oxide Electrochemistry

Abstract: Recently, the ultra-high temperature electrochemistry (UTE, about > 1000 °C) has emerged, which represents an exploration to extend the temperature limit of human technology in electrochemical engineering. UTE has farreaching impact on revolutionary low-carbon metal extraction and the in situ production of oxygen for deep-space exploration. It is hence of urgency to systematically summarize the development of UTE. In this Review, the basic concepts of UTE and the physicochemical properties of molten oxides are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Solar‐driven electrochemical CO 2 reduction hence holds promise for artificial photosynthesis. Molten salt electrolysis has a solid foundation in industrial extraction of active metals, and is recently demonstrated as a promising method to convert CO 2 into advanced energy materials for an overall carbon‐neutral utilization of CO 2 [4–8] . Electrolytic aluminum industry as the most mature application of molten salt electrochemical metallurgy process outputs over 40 million metric tons Al in 2022 in China [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solar‐driven electrochemical CO 2 reduction hence holds promise for artificial photosynthesis. Molten salt electrolysis has a solid foundation in industrial extraction of active metals, and is recently demonstrated as a promising method to convert CO 2 into advanced energy materials for an overall carbon‐neutral utilization of CO 2 [4–8] . Electrolytic aluminum industry as the most mature application of molten salt electrochemical metallurgy process outputs over 40 million metric tons Al in 2022 in China [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Molten salt electrolysis has a solid foundation in industrial extraction of active metals, and is recently demonstrated as a promising method to convert CO 2 into advanced energy materials for an overall carbon-neutral utilization of CO 2 . [4][5][6][7][8] Electrolytic aluminum industry as the most mature application of molten salt electrochemical metallurgy process outputs over 40 million metric tons Al in 2022 in China. [9] Using excess capacity of electrolytic aluminum industry to electrolyze industrial CO 2 emission can not only reduce carbon emission but also relieve the pressure of production regulations.…”
Section: Introductionmentioning
confidence: 99%